Aggregation of cation-anionic and related polymethine dyes - A. S. Tatikolov; G. Ponterini; Zh. A. Krasnaya (International Journal of Photoenergy)
Absorption, fluorescence, and fluorescence excitation spectra were studied for a number of cation-anionic and related anionic polymethine dyes in weakly polarand nonpolarsolvents, as well as in binary mixtures of solvents of different polarity. For some dyes, aggregation is observed in toluene or acetonitrile-toluene mixtures with low amounts of acetonitrile, which is revealed as appearance of new absorption bands and/or broadening of the initial bands of a monomeric dye. Solvent mixtures butyronitrilehexane with low butyronitrile content were found to greatly stimulate the formation of dye aggregates for most of the dyes studied. The absorption spectra of the aggregates are often blue-shifted with respect to the corresponding absorption spectra of parent monomeric dyes and/or represent broad continuums located both in the blue and red regions. For one of the cation-anionic dyes studied, which consists of 3,3′-diethylthiamonomethinecyanine cation and trimethinebenzoxanine anion, fluorescent aggregates were observed; their broad fluorescence band is located in the long-wavelength region. For this dye, gradual transition from nonfluorescent aggregates to fluorescent ones and then to monomeric ion pairs and dissociated ions was observed in butyronitrile-hexane mixtures with growing butyronitrile content.